Método para fermentar pequeñas cantidades de cacao - Martínez Vázquez, V.; Instituto Interamericano de Ciencas Agrícolas (IICA) (IICA, Turrialba (Costa Rica), 2014)
Tesis (Mag.Agr.) - IICA, Turrialba (Costa Rica), 1949